Analisis Perubahan Liputan Hutan Rakyat Kecamatan Geyer, Kabupaten Grobogan Tahun 2010 Dan 2015 - Rimbawan, Ardi; , Ir. H. Taryono, M.Si (2016)
The aim of the research is to identify changes in forest coverage in District Geyer, Grobogan 2010 and 2015, Analyzing the causes of changes in forest coverage in District Geyer, Grobogan 2010 and 2015. The method used is the analysis of secondary data and field surveys. In method the information (secondary data) were collected from agencies associated with this research. While the field surveys (observations, field checks) were conducted directly in the field about the condition and the situation of research areas. The results showed that: Under the Private Forest Land Coverage Map Sub district Geyer, Grobogan 2010 and 2015 extensive arca of private forcst change in Suru is the most dominat with 20,8%, 18,5% Geyer Village, 11% by Juworo Village, 9,2% by Sobo Village, 8,5% Monggot Village, 8,4% by Ledokdawan Village, 8,4% by Ngrandu Village, 3,8% by Rambat Village, 3,8% by Bangsri Village, 2,5% by Karanganyar village, 2,3% by Jambangan Village, 2% by Kalangbancar Village and 0,2% by Asemrudung Village. Asemrudung a decline of 0,16% by Asemrudung Villageand 1,06% by JambanganVillage. Table Matrix of Change of private forcst land Forest Land of the residents in 2010 and 2015 can be seen that these lands are underwent of 1058.6 hectares changes. While others, namely State Forest, Rice and Tegalan had no change of land use. From the Dinas Kehutanan dan Perkebunan policy collaborating with the local residents to direct and assist facilitating the seedling needs, fertilizer and water. In the management of open field to be forest especially for the specific trees such as Teaks, Mahogany, Acacia and others. Because of the marginal characteristic of the land is suitable to be planted and the result is beneficial to the residents to satisfy their needs. The land in the area of Geyer sub-district is not fertile for farming. Therefore the residents prefer planting their land with Teaks, Mahogany, Acacia and others. Because of the forest commodity as Teaks, Mahogany, Acacia have more economical value than farm commodity like rice and corn.